Tetraphenylethene end-capped diketopyrrolopyrrole fluorogens with AIE and large two-photon absorption cross-sections features and application in bioimaging. (October 2016) - Jiang, Tao; Li, Dongyu; Hang, Yandi; Gao, Yuting; Zhang, Hequn; Zhao, Xinyuan; Li, Xin; Li, Bo; Qian, Jun; Hua, Jianli
Abstract: In this work, a series of new diketopyrrolopyrrole-based dyes have been synthesized by connecting tetraphenylethene to the diketopyrrolopyrrole core. All the four compounds exhibit good aggregation-induced emission property with nonemissive in the solution but strong red fluorescence in the aggregate or solid state. Also, these new dyes exhibit large two-photon absorption cross sections (σ), in which the σ data measured by the open aperture Z-scan technique are determined to be 150, 300, 1140 and 1016 GM for four dyes, respectively. In addition, compound with stilbene and four tetraphenylethene units (DPP-TPE-3) was used as the luminogen and encapsulated into nanoparticles for cell imaging and two-photon excited fluorescence blood vessels imaging. The result indicates that it can be used as the effective fluorescence probe for bioimaging and has great potential for bioapplications. Graphical abstract: A series of new DPP-based derivativesDPP-TPE-(1-4) were designed and synthesized. These dyes show excellent AIE and 2PA properties, in which the success of the cell imaging and blood vessels imaging used by theDPP-TPE-3 as the luminogen indicates that it can be used as the effective fluorescence probe for bioimaging and has great potential for bioapplications. Highlights: Four diketopyrrolopyrrole-based derivatives were synthesized and characterized. These dyes have aggregation-induced emission and two-photon absorption properties. DPP-TPE-3 has the largest two-photon absorption cross sections (σ = 1140 GM). DPP-TPE-3 can be used as an effective florescence probe for bioimaging.